Military Gymnasium in Irkutsk - Sinkova, Anastasia; Selivanov, Roman (project baikal, 2021)
The article presents the results of the qualification work “Renovation of the territory of Irkutsk Higher Military Aviation Engineering School with the development of a fragment of the military gymnasium complex in Irkutsk”. The historical context, urban planning and space location of the university campus and techniques are described. They allow increasing the density of buildings and pedestrian accessibility of infrastructure facilities, which makes the urban environment more comfortable. The definition of renovation and its main characteristics are given.
Keywords: renovation; military gymnasium; urban environment; historical context; innovative technologies; interdisciplinary research